Evaluación de tres niveles de proteína sobre el crecimiento en juveniles de la vieja colorada (Cichlasoma festae). - Martillo Núñez, Hugo Alejandro (2019)
The present investigation was carried out in the "Boca Grande" property owned by Mr. Martillo, located in the Estero Grande area, Mocache canton, province of Los Ríos, Republic of Ecuador and lasted 60 days. Its geographic coordinates 0 ° 57'27 "of South latitude and 79 ° 18 '27" of West longitude, with an ecological zone of humid-tropical forest at a height of 120 msnm. The growth of an organism implies a change in size over time. This change can be measured using variables such as length or weight, the growth of fish is determined mainly by the amount of food ingested (energy and nutrients) and by the temperature of the water. Fish, like poikilothermic animals, are unable to regulate their body temperature, so their metabolism only works optimally within a range of adequate temperatures, within which ingestion and growth are maximum, but decrease when the temperature is at above or below the optimum range. The weight gain of the old colorado in the juvenile stage was higher with food of 50% protein, the size, in terms of the length in the growth of the old colorada in the juvenile stage is not influenced by the percentage of protein in the ration, all treatments being similar. However, the dimensional surface of the width was favorable for 50% protein in the ration. There was no mortality in the treatments studied.